Early Surgical Complications after Primary Cleft Lip Repair: A Report of 3108 Consecutive Cases. (November 2015) - Schönmeyr, Björn; Wendby, Lisa; Campbell, Alex
Objective: To analyze short term surgical complications after primary cleft lip repair. Patients and Design: A total of 3108 consecutive lip repairs with 2062 follow-ups were reviewed retrospectively through medical records. Patients were aged 3 months to 75 years at the time of surgery, with a median of 7 years. Setting: Guwahati Comprehensive Cleft Care Center, Assam, India. Intervention: Primary cleft lip repair. Main Outcome Measures: Documented complications in terms of dehiscence, necrosis, infection, and suture granuloma were compiled. Logistic regression was used with dehiscence (yes/no) or infection (yes/no) as binary dependant variables. Age, cleft type, and surgeon (visiting/long term) were used as covariates. Results: Among the 2062 patients who returned for early follow-up, 90 (4.4%) had one or more complications. Dehiscence (3.2%) and infection (1.1%) were the most common types of complication. Visiting surgeon, complete cleft, and bilateral cleft were significantly associated with wound dehiscence, and complete cleft was associated with wound infection according to the logistic regression analysis. Of patients with bilateral complete clefts, 6.9% suffered from some degree of wound dehiscence. Conclusion: In a setting where presurgical molding is unavailable and patients present at all ages, lip wound dehiscence is a relatively common complication in patients with bilateral complete clefts. The risk of dehiscence, however, is reduced when these cases are assigned to surgeons with experience with these types of clefts. We also found that the incidence of wound infection can be kept relatively low, even without the use of postoperative antibiotics.